A triazine-functionalized nanoporous metal–organic framework for the selective adsorption and chromatographic separation of transition metal ions and cationic dyes and white-light emission by Ln3+ ion encapsulation. Issue 29 (5th July 2019) - Yousaf, Afifa; Arif, Ali Muhammad; Xu, Na; Zhou, Jie; Sun, Chun-Yi; Wang, Xin-Long; Su, Zhong-Min
Abstract : A novel MOF1 was designed, which showed the separation of Cu 2+ ions and cationic dyes along with white light emission by the encapsulation of Ln 3+ ions. Abstract : In this study, a triazine-based nanoporous metal–organic framework (MOF1) using the tricarboxyl ligand 5, 5′, 5′′-((1, 3, 5-triazine-2, 4, 6-triyl)tris(azanediyl))tris(2-methylbenzoic acid) was solvothermally synthesized. High thermal and chemical stability of MOF1 was established by thermogravimetric and powder X-ray diffraction analysis. Owing to its porous structure with potential nitrogen chelating sites, MOF1 could selectively adsorb the Cu 2+ ions over the Mn 2+, Ni 2+, Co 2+, and Zn 2+ ions, and the chromatographic separation of the Co 2+ ion was achieved from a mixed solution containing Co 2+ and Cu 2+ . Moreover, MOF1 could selectively adsorb and separate cationic dyes on the basis of ionic selectivity rather than size selectivity. Furthermore, the nanoporous MOF1 was used as a host to encapsulate luminescent species, and it displayed a characteristic luminescent color (green for Tb 3+ and red for Eu 3+ ); moreover, we tuned the luminescence properties of the MOF1 to achieve white light emission with good color quality.